Breakfast at Tiffany's - Capote, Truman, 1924-1984. (London : Penguin Books, 2000)
Contains the title work about Holly Golightly, a Manhattan playgirl whose antics mask a pain-filled past; and includes three additional stories, "House of Flowers," "A Diamond Guitar," and "A Christmas Memory.".
Breakfast at Tiffany's -- House of flowers -- A diamond guitar -- A Christmas memory.
Adult.
Adult
Keywords: Short stories, English; United States -- Social life and customs -- Fiction; United States -- Social life and customs -- Fiction